PENGARUH INDEPENDENSI AUDITOR, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN AKUNTABILITAS TERHADAP KINERJA AUDITOR Studi Empiris pada Auditor Pemerintah di BPK Jateng - Ahmad Aji Pramana; Rohmad Yuliantoro (Universitas Ahmad Dahlan, 2013)
The purpose of this study is to determine the effect of auditor independence toward auditor's performance, leadership style toward audit performance, the organization's commitment and accountability auditor toward the performance of auditors. The object of this study was on the State Audit Board Representative of Central Java. The writer took the sampling by simple random sampling through questionnaires. Software used to test the instruments and hypothesis is SPSS version 16.0. The results of the first hypothesis in the independence of the auditor does not affect the performance of auditors, futhermore the results of the second hypothesis that leadership style does not also affect the performance of auditors. However, the results of the third hypothesis is the organizational commitment affect the performance of auditors but the results of the fourth hypothesis is accountability does not affect the performance of auditors. The results of this study should be able to provide additional information and material for relevant literature in the future.